2018
DOI: 10.3390/ijms19061703
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and Inactivation of Uropathogenic Escherichia coli Biofilms on Urinary Catheters by Sodium Selenite

Abstract: Urinary tract infections (UTI) are the most common hospital-acquired infections in humans and are caused primarily by uropathogenic Escherichia coli (UPEC). Indwelling urinary catheters become encrusted with UPEC biofilms that are resistant to common antibiotics, resulting in chronic infections. Therefore, it is important to control UPEC biofilms on catheters to reduce the risk for UTIs. This study investigated the efficacy of selenium for inhibiting and inactivating UPEC biofilms on urinary catheters. Urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 66 publications
(93 reference statements)
1
16
0
Order By: Relevance
“…Patients who are hospitalized for long periods void urine through urinary catheters [14], and long-term use of indwelling urinary catheters can cause urinary tract infections [25]. Biofilm formation by uropathogens is the most common cause of persistent infection in the genitourinary tract [26].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who are hospitalized for long periods void urine through urinary catheters [14], and long-term use of indwelling urinary catheters can cause urinary tract infections [25]. Biofilm formation by uropathogens is the most common cause of persistent infection in the genitourinary tract [26].…”
Section: Introductionmentioning
confidence: 99%
“…We are not the first to show that selenium can lead to a bacteriostatic inhibition of growth. Several studies have also shown inhibition of bacterial growth with selenium or selenium-containing nanoparticles [34] at concentrations both above [35] and below [36] the concentrations used here. Aribi et al showed that selenium supplementation of media led to inhibited growth of Staphylococcus aureus, but this effect was seen with 20 ng/ml (~0.1 μM) of sodium selenite, about a 10,000x lower concentration than tested here [36].…”
Section: Plos Onementioning
confidence: 72%
“…Recurrent UPEC infections have been related to biofilm formation, which can determine the persistence of such pathogens in the vaginal microbiota, in the bladder epithelial cells, or both [ 62 ]. In addition, in patients using a bladder catheter, bacteria can ascend to the bladder and migrate to the mucosa and catheter surfaces, favoring infection [ 63 ]. In these cases, the pathogen’s ability to adhere and form biofilms on the device results in persistent and recurrent infections in catheterized patients [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%